Design a charging station for electric vehicles in Singapore - Wang, Xiao. (2013)
Electric Vehicle (EV) is a promising technology for future transportation because of its high energy conversion efficiency and the capability to reduce pollution. Building EV charging infrastructures is a necessary condition for the wide deployment of EVs. Hence, integration strategies for energy-efficiency in buildings and transport sectors gains increasing importance. This report focuses on the one of the limiting factors known as contracted capacity. In this project, the logic of evaluating a commercial building's EV charging capability with respect to contracted capacity is investigated with a toolbox developed so that the building's energy administrator can determine the number of EVs can be charged and the number of charging stations should be built. Meanwhile, a cost and benefit analysis is also performed, which demonstrates that investing in EV charging stations is a beneficial investment option.